Comparison of Resorbable Plating Systems: Complications During Degradation - Nguyen, Dennis C. (J Craniofac Surg, 2017)
INTRODUCTION: Several bioresorbable plating systems have become standard in pediatric craniosynostosis reconstruction. A comparison of these systems is needed to aid surgeons in the preoperative planning process. We aim to evaluate one institution’s experience using Resorb X® by KLS Martin and Delta Resorbable Fixation System by Stryker (Stryker Craniomaxillofacial, Kalamazoo, MI). METHODS: A sample of patients with single-suture nonsyndromic craniosynostosis treated at St. Louis Children’s Hospital between 2007 and 2014 using either Resorb-X or Delta bioresorbable plating systems were reviewed. Only patients with pre-operative, immediate and long-term 3D photographic images or computed tomography scans were included. A comparison of plating system outcomes was performed to determine the need for clinic and emergency room visits, imaging obtained, and incidence of subsequent surgical procedures due to complications. RESULTS: Forty-six patients (24 Resorb-X and 22 Delta) underwent open repair with bioabsorbable plating for single suture craniosynostosis. The mean age at each imaging time point was similar between the two plating systems (p>0.717). Deformity-specific measures for sagittal (cranial index), metopic (inter-frontotemporale) and unicoronal (frontal asymmetry) synostosis were equivalent between the systems at all time points (0.05<p<0.904). A single Delta patient developed bilateral scalp cellulitis and abscesses and subsequently required operative intervention and antibiotics. CONCLUSION: Bioabsorbable plating for craniosynostosis in children is effective and has low morbidity. In our experience, we did not find a difference between the outcomes and safety profiles between Resorb-X and Delta.